The Flow and Fracture of Cracked Ice: Experiments to Aid Modeling - Schulson, Erland M (1999)
The ultimate goal of this work is to contribute new physical insight to the development of the next generation sea ice model, PIPS 3.0. More specifically, it is to understand the processes underlying the deformation of first-year sea ice covers, from the formation of oriented leads to the frictional sliding of individual floes. The objective is to test the hypothesis that first-year sea ice covers deform through a combination of continuum and granular flow. It is suggested that continuum flow controls deformation until slip lines develop, at which point granular flow governs. With this in mind, the near-term objectives are to study and understand the mechanical behavior of columnar sea ice deformed in the laboratory under controlled conditions and then to compare behavior on the small scale with that on the large scale. The second hypothesis to be tested is that the physical processes underlying the compressive failure of ice are independent of spatial scale.